HUBUNGAN POLA ASUH ORANGTUA DENGAN KEMAMPUAN TOILET TRAINING PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS KARANGGEDE BOYOLALI - Rismawati; AP, Atik Mahmudah (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2022)
One of the child development tasks in childhood is toilet training. The successed of the toilet training depends on the prepared of the children and the parents. One of which is formed in the parenting method. The aim study was to know about the correlation between parenting method with toilet training skill at children aged 18-59 month in working area of the health center Karanggede Boyolali, District Boyolali. Methods this study was correlational descriptive research with cross-sectional approach. Population in this study was all parents that have children aged 18-59 month in working area of the health center Karanggede Boyolali, District Boyolali. Total population was 2250 parents. The sample in this study was taken proportionaterandom sampling, with total sample 96 respondents. Instrument in this study using questionnaire, observation sheets and data analyzed using spearman. The result showed 70 respondents (72,9%) parents used democratic parenting, most respondents 52 respondents (54,2%) had good toilet training skill. There was correlation between parenting method with toilet training skill atchildren aged 18-59 month with the result analyzed significant value 0,0001<0,05. There was correlation between parenting method with toilet training skill at children aged 18-59 month in working area of the health center Karanggede Boyolali, District Boyolali.